Kenya : Report on the Observance of Standards and Codes (ROSC) Data Module. (IMF Staff Country Reports; Country Report ;, 2005)
This report on Kenya's Observance of Standards and Codes presents Data Module, response by the authorities, and detailed assessments using the data quality assessment framework. With regard to serviceability, Kenya either meets or exceeds the General Data Dissemination System recommendations for periodicity and timeliness for all disseminated data. Efforts to enhance the accessibility of statistics have also met a certain degree of success, although greater attention should be paid to improving the utility of statistical products and the procedures for data dissemination.